Firm-level determinants of business tax evasion in emerging economies: The case of Argentina; Determinantes microeconómicos de la evasión tributaria empresarial en economías emergentes - Florencia Verónica Pedroni; Anahí Briozzo; Gabriela Pesce (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
This paper aims to identify the determinants of revenue underreporting and their temporal evolution from a business perspective in formal firms located in an emerging country with high inflation (Argentina). We propose a conceptual model and we estimate it empirically using a logistic regression based on pooled data 2010-2017 of the World Bank Enterprise Surveys. The findings show that revenue underreporting is a multicausal phenomenon where taxes lose importance in the light of other determinants such as: corruption, regulation and bureaucracy, quality of public and government services, detection probability, sector informality and political instability. Moreover, the outcomes recognize companies' characteristics with a greater propensity to underreport sales (smaller size, selling in domestic market, from manufacturing sector, without external financing, with male entrepreneurs). Our empirical evidence is relevant for the formulation of public policies aimed at reducing revenue underreporting.
Keywords: E26; H26; O17; M21; D22; H32; 330; informal sector; revenue underreporting; tax; corruption; bureaucracy; institutional quality; emerging economy